Маркери розпаду жанрово-стильової системи літератури другої пол. ХХ ст. - Наливайко, Д.С. (Слово і Час, 2019)
У статті розглянуто трансформаційні процеси, що відбувалися в літературі на рівні її жанрово-стильової типології. Проаналізовано роль у цьому процесі “нового роману”, “літератури факту”,
наукової фантастики, новітнього міфологізму, інтелектуальної прози, драматургії й поезії, а також
естетики постмодернізму з її зміною співвідношення між творчо-оригінальним і повторюваним,
парафразованим на користь другого – явище “центонності”. The article focuses on the transformation processes that took place in literature at the level of
its genre and style typology. In the 2nd half of the 20th century certain genres and types of writing
acquired meanings and functions of styles. It could be one of the most widespread or even dominant
genres (for example, ‘new novel’), a type of fi ction (modern ‘literature of fact’), a genre of literature at
the border with other kinds of spiritual and creative activity (essay, biography, etc.). The functioning in
a literary process made them close to styles and literary trends and changed their basic code. Usually
they acted as dominant ramifi ed genres or types of writing subordinating other (marginal) genre forms.
A paradigmatic feature of a ‘new novel’ is convergence of literature and science, writers and
scientists. Due to scientifi c and technical revolution the criterion of accuracy and appreciation of real
fact and document took an important place in a writer’s conscience. The ‘aesthetics of fact’, formed
on this ground, gave a basis for the non-fi ctional genres in the 20th-century literature. The use of
ready ‘blocks of life’ in the non-fi ction of the 2nd half of the 20th century is tightly connected to acute
conceptuality and often to apparent journalism. The writer’s imagination was focused on revealing
semantic and artistic potential of the real facts.
The intellectual prose, dramaturgy and partly poetry were full of genres and genre varieties with
strict semantic and imaginative structure, aimed to express certain generalizations and actual world
view ideas. These are novels-parables, novels-allegories, novels-symbols, and others like that. The
theme and motive construct, especially in its mental and epistemological aspect, became frequent
in a lyrical poetry. It was the way of forming the metagenre concepts of philosophical and meditative
lyrical poetry, as well as, in particular, metaphysical, prophetical, suggestive, intimate, social, and
journalistic one, with their inherent main codes.
The process of leveling and destructing the traditional genres, styles, and their systems in
postmodernism, as well as recombining their components, resulted in emergence of numerous hybrid
forms. The ratio of original and repetitive or paraphrased material in the literary works began to change.